Ameloblastoma: reporte de diez casos y revisión de la literatura - Duque-S., Francisco Levi; Radi-L., José N.; Del Valle-R., Andrés Felipe (Revista Facultad de Odontología Universidad de Antioquia, 2009)
Ameloblastoma is the most common benign tumor, It represents 1% of all odontogenic tumors and comprises 11 to 18% of all maxillary lesions. Eighty percent of the cases described are located in the body of the mandible and its angle; it affects males and females equally, and its more prevalent during the third and fourth decades of life. This tumor has diverse clinical, radiographical and histo-pathological aspects. Although it is considered a benign pathology, it is locally invasive and has a high rate of recurrence. The objective of this article is to present the experience obtained with the diagnosis and treatment of ten cases of ameloblastoma in patients ranging from 12 and 73 years of age. Eighty percent of theses cases were located in the mandible and were causing different clinical manifestations such as: facial asymmetry, dental displacement, root resorption, alteration in the occlusion, pain, masticatory difficulty and pathological fractures. According to their image a radiographic classification was made, identifying them as unilocular and multilocular. Histopathologically, they were grouped according to the observed variant. Different treatment alternatives are described, as well as the complications encountered. Two patients had previous surgery for dentigerous cysts in the same area. Two cases had recurrent ameloblastoma five years after their surgical interventions performed in other institutions.